Assessing General Health of Staff Affiliated to Tehran University of Medical Sciences Hospital and Its Related Factors in 2014 - Yeganeh Hayati; Hojjat Rahmani; Mohammad Arab (Tehran University of Medical Sciences, 2017)
Background: Health of hospital staff has a determinant role in increased productivity and since the main mission of hospitals is community health promotion, in order to achieve this important issue, monitoring, maintaining and improving general health is essential; this study developed to assess general health of staff affiliated to Tehran University of Medical Sciences and identify its related factors. Materials and Methods: This Cross-Sectional, Descriptive-analytical study was conducted among 320 staff members of the Tehran University of Medical Sciences who selected using random sampling. In order to data collection, the General Health questionnaire was used. Collected data were analyzed using SPSS software through t-test and ANOVA tests. Results: Study findings revealed that 47.5% of participants had psychological disorders suspiciously; prevalence of physical symptoms, anxiety, social dysfunction and depression were 53.9%, 49.3%, 79.5% and 14.6% respectively. There was a significant relation between general health and demographic features such as gender, marital status, major, job department, housing situation and type of employment (p<0.05).  Also, the personal characteristics of managers influenced on the general health staff. Conclusion: General Health of staff in hospitals Tehran University of Medical Sciences in comparison with similar studies at inside and abroad is not in good condition, therefore, it is recommended that policy makers and managers concerned the programs and solutions towards priorities in order to promote health personnel.